Occupational stressors in nurses and nursing adverse events - Azam Karimi; Marzieh Adel-Mehraban; Mahin Moeini (Wolters Kluwer Medknow Publications, 2018)
Background: Nursing adverse events (AEs) are well-defined problems in the healthcare system and may have irreparable consequences. Due to the complexity of care, many factors contribute to AEs and affect patient safety, one of which is occupational stress. The present study aimed to determine the relationship between nursing AEs and occupational stress in nurses in centers affiliated to Isfahan University of Medical Sciences, Isfahan, Iran, in 2015. Materials and Methods: In this descriptive correlational study, the participants were selected through random and quota sampling methods. The data collection tool was a three-part questionnaires consisting of a demographic characteristics form, the Nurses' Job Stress Questionnaire, and Nursing Adverse Events Questionnaire. Descriptive and analytical statistics were used to analyze the data in Statistical Package for the Social Sciences software. Results: Among the four factors affecting occupational stress in nurses, administrative factors had the highest impact; subsequently followed, by environmental factors and interpersonal factors. The mean score of AEs was reported as 30 cases per year. There was a significant correlation between the overall mean score of occupational stress and AEs (r = 0.12, p = 0.04). Conclusions: According to the results of this study, moderate to high levels of job stress were observed among nurses. The results also showed that occupational stress can lead to nursing AEs. Given that nurses believe the highest mean of occupational stressors is related to administrative factors, an appropriate and comprehensive leadership is necessary to improve the current conditions.